PERBANDINGAN PENINGKATAN KADAR GLUKOSA DARAH ANTARA MADU HUTAN DAN GULA PASIR PADA MENIT KE - 30 TERHADAP DEWASA MUDA SEHAT YANG BERPUASA SELAMA 8 JAM - RAHMI AGINTA ULFAH; SITI HAJAR (LP2MTBM MAKARIOZ, 2020)
Background : Glucose is the most important carbohydrate in mammalian biochemistry because almost all carbohydrates infood are converted to glucosa for metabolism. Objective : The purpose of this study is determine the differences in theincrease in blood glucose levels after giving forest honey and granulate sugar in the 30th minute to student who fasted.Method : The type of this study is True Experiment with a pretest-postest with control group design. This research techniqueuses a total sample. The data analysis using is Independent Sample T Test. The way to collect data is at one time in twogroups and then the result are compared and analyzed. Subject in this study were healthy young adults in December 2018 –January 2019 which consisted of 22 respondendents and divided into two groups which is 11 respondents in the group weregiven forest honey and 11 subjects in the group were given sugar. Result : There is differences in blood glucose levelsbetween forest honey and granulate sugar after 30 minutes ( p.value <0,05). Conclusion : There is the difference betweengiving honey and giving granulate sugar in the 30th minute to blood glucose levels young adults who fasted.